2005
DOI: 10.1007/s00414-005-0013-6
|View full text |Cite
|
Sign up to set email alerts
|

A new “miniSTR-multiplex” displaying reduced amplicon lengths for the analysis of degraded DNA

Abstract: A multiplex PCR was designed for the loci D2S1338, D16S539, D18S51, TH01 and FGA using redesigned primers in order to reduce the lengths of the amplification products compared to the designs used in commercially available multiplex PCR kits, also including amelogenin. The new PCR primers were used to amplify highly degraded DNA from casework samples, which had shown no or only poor results for these loci in previous analyses with standard primer sets. The application of the new miniSTR-multiplex resulted in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 20 publications
1
67
0
3
Order By: Relevance
“…The results were collated and analysed and, in general, mini-STR systems were shown to be the most effective [26]. Since then, a number of other studies have demonstrated that successful analysis of degraded DNA specimens from mass disasters or compromised forensic evidence improves with smaller-sized PCR products [8,10,12,14,[27][28][29][30][31]. The TIMELINE (Figure 1) shows the progress of ChrX miniSTRs over the years [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46].…”
Section: History and Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results were collated and analysed and, in general, mini-STR systems were shown to be the most effective [26]. Since then, a number of other studies have demonstrated that successful analysis of degraded DNA specimens from mass disasters or compromised forensic evidence improves with smaller-sized PCR products [8,10,12,14,[27][28][29][30][31]. The TIMELINE (Figure 1) shows the progress of ChrX miniSTRs over the years [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46].…”
Section: History and Progressionmentioning
confidence: 99%
“…Bacteria are the main agents on land while fungi are responsible for oceanic degradation [6,7]. Slightly degraded samples can be typed by traditional STRs, but may yield negative results as the fragmentation increases [8][9][10]. Conventional STRs have a size range of 100-400 bp most of which consists of flanking sequences on both sides of the repeat region.…”
Section: Introductionmentioning
confidence: 99%
“…This is known to result in an increased success rate when degraded DNA is investigated [17] and therefore highly appreciated in forensic analysis.…”
Section: Mass Spectrometric Str Analysismentioning
confidence: 99%
“…As a result of the high temperature exposure, the DNA available for analysis is highly thermally degraded and frequently present in very few copies. A trace amount of template DNA available for amplification very frequently leads to different types of artifacts such as a lack of amplification of particular alleles (allele drop-out) or loci (loci drop-out) [7][8][9][10]. The problem of the effect of high temperature on biological material and the possibility of DNA identification has been rarely mentioned.…”
Section: Introductionmentioning
confidence: 99%
“…DNA yield and stability in different soft human tissues vary substantially [14] and are highly dependent on physical and chemical factors. In many cases reduction of amplicon size, like substituting STR (Short Tandem Repeats) with miniSTR loci or SNPs, can drastically improve DNA typing results [9,11,12,15].…”
Section: Introductionmentioning
confidence: 99%